Dampak Responsible Leadership, Reciprocity, Trust, Knowledge Sharing Intention, dan Helping Behavior terhadap Knowledge Sharing Behavior pada Organisasi Mahasiswa - Aqdas Dawami; Dimas Angga Negoro (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyse the impact of Responsible Leadership, Reciprocity, Trust, Knowledge Sharing Intention, and Helping Behavior on Knowledge Sharing Behavior in student organisations. The research method used was a quantitative survey by distributing questionnaires to members of various student organisations at several universities in the Jabodetabek area, and the sample used in the study amounted to 165 respondents using multiple linear regression analysis and data collection techniques using purposive sampling. The analysis results show that Responsible leadership, Reciprocity, Trust, Knowledge Sharing Intention, and Helping Behaviour have a significant influence on Knowledge Sharing Behaviour. Overall, these findings underscore the importance of responsible leadership, reciprocity, trust, knowledge sharing intention, and helping behaviour in encouraging knowledge sharing behaviour among members of student organisations. This research also provides insights for student organization managers in designing strategies that can strengthen knowledge-sharing behavior among their members. Practical implications of this research can help student organizations improve the culture of knowledge sharing and collaboration in academic environments.